Plasmodium stage-selective antimalarials from Lophira lanceolata stem bark. (June 2020) - Soré, Harouna; Lopatriello, Annalisa; Ebstie, Yehenew A.; Tenoh Guedoung, Alain R.; Hilou, Adama; Pereira, José A.; Kijjoa, Anake; Habluetzel, Annette; Taglialatela-Scafati, Orazio
Abstract: Targeting the transmissible stages of the Plasmodium parasite that develop in the human and mosquito host is a crucial strategy for malaria control and elimination. Medicinal plants offer a prolific source for the discovery of new antimalarial compounds. The recent identification of the gametocytocidal activity of lophirone E, obtained from the African plant Lophira lanceolata (Ochnaceae), inspired the evaluation of the plant also against early sporogonic stages of the parasite development. The bioassay-guided phytochemical study led to the isolation of two known lanceolins and of a new glycosylated bichalcone, named glucolophirone C. Its stereostructure, including absolute configuration of the bichalcone moiety, was elucidated by means of NMR, HRMS, ECD and computational calculations. Lanceolin B proved to be a potent inhibitor of the development of Plasmodium early sporogonic stages indicating that the plant produces two different stage-specific antimalarial agents acting on transmissible stages in the human and mosquito host. Graphical abstract: Phytochemical study of Lophira lanceolata afforded lanceolin B, an inhibitor of Plasmodium early sporogonic stages, and the new bichalcone glucolophirone C. Image 1 Highlights: The glycosylated bichalcone glucolophirone C has been isolated from Lophira lanceolata . The absolute configuration of the bichalcone Lophirone C has been determined. Lanceolin B is a potent inhibitor of the development of Plasmodium early sporogonic stages. Lophira lanceolata produces two different stage-specific antimalarial agents acting on transmissible stages.